2006
DOI: 10.3892/or.15.3.539
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 14 expression in colorectal cancer is associated with liver and lymph node metastases

Abstract: Ubiquitin-specific protease 14, also known as the 60 kDa subunit of tRNA-guanine transglycosylase (USP14/ TGT60kD), belongs to the ubiquitin-specific processing protease (UBP) family. USP14/TGT60kD expression in leukemic and colorectal cancer cell lines, and the suppression of such an expression after the induction of cell differentiation have been reported. In the present study, we attempted to clarify whether USP14/TGT60kD overexpression affects the clinicopathological features of colorectal cancer. Immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 15 publications
4
50
0
Order By: Relevance
“…[29][30][31] Although USP14 and UCHL5 have been implicated in the tumorigenesis and progression of colorectal cancer and esophageal squamous cell carcinoma, 14,19 their role in MM is undefined. Consistent with previous studies, 15,16,21 we found that USP14 and UCHL5 are highly expressed in MM cells vs normal plasma cells and PBMCs, suggesting a role of USP14 and UCHL5 in MM pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Although USP14 and UCHL5 have been implicated in the tumorigenesis and progression of colorectal cancer and esophageal squamous cell carcinoma, 14,19 their role in MM is undefined. Consistent with previous studies, 15,16,21 we found that USP14 and UCHL5 are highly expressed in MM cells vs normal plasma cells and PBMCs, suggesting a role of USP14 and UCHL5 in MM pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although neither USP14 nor UCHL5 appears to be essential for cell survival alone, dual knockdown using RNA interference has been shown to lead to the accumulation of polyubiquitinated substrates and loss of cell viability (Koulich et al, 2008;Tian et al, 2013;Wang et al, 2014). Interestingly several reports have shown that USP14 is consistently overexpressed in solid tumours of lung and ovarian origin and associated with metastases in colorectal carcinoma suggesting a potential role in oncogenesis (Shinji et al, 2006;Wang et al, 2015;Wu et al, 2013). Considering that USP14 and UCHL5 belong to different classes of DUBs, dual inhibition of these enzymes by small molecules would a priori be expected to be possible only in the context of broad-spectrum DUB inhibition.…”
Section: Proteasomal Dubs As Drug Targets For Cancer Therapymentioning
confidence: 99%
“…IU1 treatment enhanced proteasome efficiency in vitro, with resultant degradation of the tau protein in initial studies. The clinical utility of a specific USP14 inhibitor may merit more attention, as new studies indicate that USP14 activity is necessary for WNT/ β-catenin signaling that is active in some cancers, and that high levels of USP14 correlate with gastrointestinal cancer severity and lung cancer mortality (54,55). To this end, bAP-15 is a recently developed compound that antagonizes USP14 and another proteasome-associated DUB, USP5, and displays antiproliferative activity in vitro and tumoricidal activity in animal models (56).…”
Section: Therapeuticsmentioning
confidence: 99%